Use Value of Plant Spesies For Steam Bath Oukup, Karo - Rima Pratiwi Batubara; Ervizal A. M. Zuhud; Rachmad Hermawan; Rusmin Tumanggor (Media Konservasi, 2017)
The use of plants in the steam bath oukup longstanding. This traditional knowledge has not been well documented. This study aims to determine the use of plants as traditional medicine through oukup by Karo people in the District Berastagi, Karo. This study uses a structured interview with the determination of respondent snowball sampling. Data were analyzed by calculating the value of plant species or species to the Use Value (SUV). The results of the study identified 69 species used in oukup. SUV plant species that have the highest of Zingiber officinale (ginger) with results of 2,30. Keywords: oukup, plant medicine, species use value